MicroRNA-30-3p Suppresses Inflammatory Factor-Induced Endothelial Cell Injury by Targeting TCF21 - Zhenyu Zhou; Yu Chen; Dongying Zhang; Shiyong Wu; Tao Liu; Guoqiang Cai; Shu Qin (Hindawi Limited, 2019)
Atherosclerosis is one of the leading causes of mortality worldwide. Growing evidence suggested that miRNAs contributed to the progression of atherosclerosis. miR-30-5p was found involved in various diseases. However, the role of miR-30-5p in regulation of atherosclerosis is not known. Here, we aim to investigate the effects of miR-30-5p on regulating the progression of atherosclerosis. The expression levels of miR-30-5p in serum collected from atherosclerosis patients and normal healthy people were analyzed by qRT-PCR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway bioinformatics were carried out to reveal the possible signaling pathways involved in the mode of action of miR-30-5p. A potential target gene of miRNA-30-5p was searched and examined by a luciferase reporter assay. ELISA, Western blot, proliferation, and flow cytometry assays were performed to assess the biological functional role of miR-30-5p in vitro. Also, an in vitro monocyte-endothelial cell coculture model was used to study the functional role of miR-30-5p in atherosclerosis. We found that miR-30-5p was significantly decreased in serum samples from atherosclerosis patients compared with control subjects. GO and KEGG analysis results showed that miR-30-5p is highly associated with genetic profile of cardiovascular disease. TCF21 was verified as a target gene of miR-30-5p. Overexpression of miR-30-5p in THP-1 not only protected endothelial cell viability but also inhibited endothelial cell apoptosis, and similar results were observed in cells with that of TCF21 knocked down. Moreover, miR-30-5p decreased the expression levels of lactate dehydrogenase (LDH) and tumor necrosis factor-α (TNF-α) and reduced reactive oxygen species (ROS) accumulation. NF-κB and MAPK/p38 pathways played an indispensable role in the protection ability of miR-30-5p against atherosclerosis. Our results reveal that miR-30-5p suppresses the progression of atherosclerosis through targeting TCF21 in vitro. Therefore, the miR-30-5p-TCF21-MAPK/p38 signaling pathway may be a potential biomarker or therapeutic target in atherosclerosis.